Serum FRAP Levels and Pre-eclampsia among Pregnant Women in a Rural Community of Northern India - Anant Gupta (Journal of Clinical and Diagnostic Research, 2016)
Introduction: There is a balance between the oxidative and the anti-oxidative forces in human body. Some studies document decreased level of anti-oxidant in pre-eclampsia while other studies showed normal level of anti-oxidant in pre-eclampsia and the evidence is equivocal. Aim: The aim of the present study was to assess enzymatic antioxidant activities in pre-eclamptic women and compare it with normotensive pregnant women with period of gestation between 28 to 36 weeks. Materials and Methods: A community-based cross-sectional survey was conducted (from November 2012-December 2013) at the Ballabgarh Health and Demographic Surveillance System (HDSS) site which was managed by Centre for Community Medicine, All India Institute of Medical Sciences, New Delhi, India. All registered pregnant women with period of gestation between 28 weeks – 36 weeks were eligible for inclusion in the study. All eligible pregnant women were contacted through home visit. A total of 217 pregnant women were enrolled out of which 209 blood samples were collected from pregnant women. About three ml of blood from antecubital vein was drawn without use of tourniquet, under aseptic conditions. It was later analysed for the serum anti-oxidative measures {Malanoaldehyde, Vitamin C, Ferric Reducing Ability of Plasma (FRAP) levels}. Data were entered on Epi-Info version 3.5.4. Data management and analysis was carried out in Stata 11. The means were compared using t-test and p-value stated. Categorical data was analysed using chi-square test. Logistic regression was used and adjusted p-value was stated. Results: A total of 217 pregnant women were eligible for the study and all were enrolled. Out of the 217 blood samples collected, eight samples accidently got destroyed. A total of 28 out of remaining 209 pregnant women (13.4%) had pre-eclampsia. Mean age (SD) was 22.4 (2.3) years, mean height (SD) was 156.6 (6.9) cm, mean weight (SD) was 65.1 (9.7) kg in pre-eclampsia group. In preeclampsia group mean serum levels of malanoaldehyde, vitamin C and FRAP was 4.2 (0.26) ng/dl, 0.83 (0.11) mg/dl, 678.0 (35.6) µmol/L. It was 4.5 (0.09) ng/dl,0.88 (0.03) mg/dl, 599.3 (13.3) µmol/L in normotensive pregnant women group respectively. The difference was statistically significant for FRAP levels only. Conclusion: Serum anti-oxidant levels are not raised among women with pre-eclampsia.